2015
DOI: 10.1038/ng.3431
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting genetic architectures of schizophrenia and other complex diseases using fast variance-components analysis

Abstract: Heritability analyses of GWAS cohorts have yielded important insights into complex disease architecture, and increasing sample sizes hold the promise of further discoveries. Here, we analyze the genetic architecture of schizophrenia in 49,806 samples from the PGC, and nine complex diseases in 54,734 samples from the GERA cohort. For schizophrenia, we infer an overwhelmingly polygenic disease architecture in which ≥71% of 1Mb genomic regions harbor ≥1 variant influencing schizophrenia risk. We also observe sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
525
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 460 publications
(563 citation statements)
references
References 66 publications
(139 reference statements)
26
525
2
4
Order By: Relevance
“…These risk loci are enriched in genes containing de novo mutations in schizophrenia, autism (MIM: 209850), and intellectual disability, 15 and several identified loci contain genes relevant to major hypotheses of schizophrenia etiology, including DRD2 (MIM: 126450; the target of antipsychotic drugs) and genes involved in glutamatergic neurotransmission (GRM3 15 One of the most striking findings that emerged early in schizophrenia studies-at the stage where there were only a handful of genome-wide-significant loci-was the highly polygenic nature of the common variants contributing to risk. 14 This observation has been widely replicated, and estimates are that 71% of 1 Mb genomic regions have at least one variant influencing schizophrenia risk, 53 and there is evidence of substantial pleiotropy with other psychiatric disorders. 26 However, genetic architecture, described as the mix of rare and common variants, is likely to differ between psychiatric disorders, as is already being observed for the higher rates of rare, de novo penetrant CNVs and single-nucleotide variants found in autism than in schizophrenia or bipolar disorder.…”
Section: Schizophreniamentioning
confidence: 98%
See 1 more Smart Citation
“…These risk loci are enriched in genes containing de novo mutations in schizophrenia, autism (MIM: 209850), and intellectual disability, 15 and several identified loci contain genes relevant to major hypotheses of schizophrenia etiology, including DRD2 (MIM: 126450; the target of antipsychotic drugs) and genes involved in glutamatergic neurotransmission (GRM3 15 One of the most striking findings that emerged early in schizophrenia studies-at the stage where there were only a handful of genome-wide-significant loci-was the highly polygenic nature of the common variants contributing to risk. 14 This observation has been widely replicated, and estimates are that 71% of 1 Mb genomic regions have at least one variant influencing schizophrenia risk, 53 and there is evidence of substantial pleiotropy with other psychiatric disorders. 26 However, genetic architecture, described as the mix of rare and common variants, is likely to differ between psychiatric disorders, as is already being observed for the higher rates of rare, de novo penetrant CNVs and single-nucleotide variants found in autism than in schizophrenia or bipolar disorder.…”
Section: Schizophreniamentioning
confidence: 98%
“…Estimates from data available to date provide the first evidence for different genetic architectures between diseases, 50 for example, there is more signal from rare variants for amyotrophic lateral sclerosis (motor neuron disease [MIM: 105400]) than for schizophrenia 51 and more predicted loci for schizophrenia than for immune disorders 52 and hypertension. 53 Theoretical and empirical observations suggest a place for non-additive genetic variation, and there have been many largely unsuccessful attempts to detect epistasis with GWAS data. There are a number of likely explanations.…”
Section: Pleiotropy Is Pervasivementioning
confidence: 99%
“…[52][53][54][55][56] Second, stratified LD-score regression analyzes summary-level data and thus does not take advantage of the additional information available in individual-level data. Although functional-enrichment analyses of individual-level data can be performed with restricted maximum likelihood (REML) and its extensions, [57][58][59] those methods are applicable only to a small number of non-overlapping functional annotations; to our knowledge, all current methods that are applicable to a large number of overlapping functional annotations are based on summary statistics, 60 whereas analyzing one annotation at a time can produce severely biased results (see Figure 2b from Finucane et al…”
Section: Discussionmentioning
confidence: 99%
“…It is striking that our study provides strong statistical evidence for the aggregate effect across 3,915 EGs impacting risk for this neurodevelopmental disorder. A recent SNP-based heritability study reported the extreme polygenicity of schizophrenia, with 70% of 1-Mb genomic regions harboring schizophrenia risk alleles (49). Assuming a similar genetic architecture in ASD and schizophrenia, genomic maps of EGs with "surviving" deleterious and regulatory variants in ASD probands represent a complementary approach for the analysis of combinations of culprit genes or alleles.…”
Section: B C Amentioning
confidence: 99%